Virtual fictional/factual positioning as an approach to the postmodern sense of the self and its dialogical dimensions in Paul Auster's selected novels - Barani, Forough (2013)
In this thesis I coin the concept of “Virtual Fictional/ Factual Positioning” (VFP), in the dialogical relationship of the author and the hero, and define it as a methodological approach to the analysis of literary narratives. VFP originates from contributions to psychological studies by Hubert Hermans in Dialogical Self Theory (DST) and the dialogical view of the relationship of author and hero in aesthetic forms by Mikhail Bakhtin in literary studies. By virtue of its interdisciplinary nature, VFP evaluates self-narratives and identifies the possible dialogical participation and coalition of the protagonists’ positions as “I-as-artist/ novelist” and “I-as-the-hero-of-my-story” amongst other positions in the novel. Nearly two decades after the emergence and development of Dialogical Self Theory (DST), the literature indicates that far too little attention has been paid to the study of literary texts in the light of it. The present research carries out a qualitative study of three selected novels by the American novelist Paul Auster (1947–), Oracle Night (2003), Travels in the Scriptorium (2006) and Man in the Dark (2008), to examine polyphonization of the self in the context of selected postmodern novels. The protagonists of these novels are themselves authors who create a hero in the paratextual story within the main story; therefore, these protagonists/ authors are very central to this dialogical study of the self. This study addresses the following questions: (1) whether the postmodern selves of the protagonists of the selected novels are polyphonized dialogical voices or are merely a cacophony of various thoughts with fewer logical and no dialogical qualities; (2) whether the hero created by the protagonist/ novelist is a possible position among his other internal and external positions. VFP examines virtual fictional and factual positioning in the confrontation between author and hero and then in the encounter between the author’s central position and a probable developing one. Consequently, the “core act of coalition” in VFP occurs within the intrinsic and simultaneously inclusive relatedness of the author and his hero’s selves’ domains. For the purpose of the present qualitative research, Hermans’ Personal Position Repertoire (PPR) method is adopted to identify, cluster and analyze I-positions. In analyzing the self-repertoire of the protagonists/ authors, the promoter and meta-position and their significant role in their lives are determined. Besides, by making use of Hermans’ questions to elicit valuations, different types of valuations are traced and discussed in the self-narratives of the characters. By doing so, this research aims to bring to the literary research community: (1) a revived interest in Bakhtin and his writings on the author/ hero relation; and (2) a reformulation of DST in the act of self-reflection in light of (1). The findings of this study demonstrate that in order to get meaning out of their supposedly meaningless lives, these protagonists/ authors are in an active dialogical relationship with their own selves – remembering, lamenting and articulating their past lives. Moreover, the results accurately establish that with reference to the postmodern self of these literary characters, the “freedom-seeker” functions as a meta-position that helps the protagonists/ authors to form a convincing dialogical space in their self-repertoire. Moreover, the “I-as-the-storyteller” or “artist/ novelist” position is identified as the promoter position. Thus, under the influence of a dynamic course of positioning and repositioning, the postmodern self of the protagonists/ authors in the selected novels demonstrates a significant degree of dialogical self by letting go of their past, dealing with their present and generating a perspective for their future – and as a result responding to their postmodern situation in quite a dialogical manner.